Report
1941-11 038-0024-006 8 There are to-day only three adult refugees in receipt of regular weekly maintenance, the remainder are all in work. Great efforts have also been made to help them learn the English language so that they could obtain more skilled employment. Many are earning very good wages. Some of the men now have Post Office Books and a good many send help regularly to their families in Spain or S. America. 36 are now known to have Aliens' War Service Permits, and more are pending. Many are members of Friendly Societies and of Trade Unions, and as their work becomes more skilled the numbers are increasing. The success of this Department since the war here was, until May, 1941, largely due to the work of Mrs. Brinton and Miss Vulliamy whose personal sympathetic and friendly handling of every case has done much to give them hope for the future and stimulate them to make good in their new life. For reasons of economy and because the majority of the refugees are now self-supporting and work easier to find, this separate branch of the work has now been brought under the care of the General Secretary, Mrs. Miller, who with the help of a Spanish assistant deals with the many problems an adult refugee still has to face. One of the most important branches of the work is to see that the men get jobs which make use of their special skill and experience — so that they can most usefully contribute to the war effort. This helps tremendously to restore their self-respect and give them a more normal outlook. Where they enter the Government Training Centres, they are most successful and pass the tests during the training; many in record time. Some of the professional soldiers have joined military groups once more, and as they move about the country, efforts are made to put them in touch with sympathetic organisations and individuals who will advise and help with the many problems a foreigner has to face in a strange country. BASQUE CHILDREN. To-day, out of the original 4,000 children, only some 416 remain. The rest have been repatriated. Many hostels have therefore been closed and the local Committees disbanded. This repatriation was a terrific undertaking. The Spanish War was hardly over before a start was made in sending the children back to their parents, wherever there was a home to receive them; no matter how poor. The business proved hard and took much 292/946/38/24(VI)